Pengaruh Literasi Keuangan, Persepsi Kemudahan Dan Persepsi Risiko Terhadap Minat Investasi Di Platform Financial Technology (Fintech) Peer to Peer Lending (Studi Kasus pada Mahasiswa di Kota Malang) - Hotijah, Hotijah; Malikah, Anik; Bastomi, Muhammad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Acting as a middleman between lenders and borrowers, financial technology (Fintech) lending combines technical innovations with financial institutions to enable various financial services. The fast spread of fintech offers investors great chances to improve the efficiency of their investments. The objective of this paper is to investigate the elements influencing investment interest in peer-to-peer (P2P) fintech lending platforms: financial literacy, perceived simplicity of usage and perceived risk. This study uses a quantitative approach using information from 150 respondents, Malang City students familiar with fintech lending services. SPSS program was used for analysis of the collected data. Investment interest is shown to be favorably influenced by financial knowledge, perceived ease of usage, and perceived risk. Under close inspection, financial literacy has no appreciable effect on investing interest. The results imply that students' desire to invest in fintech loan platforms is much influenced by their perceived risk and simplicity of usage. Keywords: Financial Technology, Fintech Lending, Financial Literacy, Investment Interest.